BUSINESS ANALYSIS OF SALTED FISH PROCESSING IN PONDOK BATU VILLAGES SARUDIK SUBDISTRICT SIBOLGA DISTRICT NORTH SUMATRA PROVINCE - Rolf Geffken; Hendrik '; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on July, 2016 in Pondok Batu Villages, Sarudik Subdistrict, Sibolga District, North Sumatra Province. This study was aimed to analyzed the input, process, output in analysis of salted fish processing, determine the investment and profits as well as analyzing the prospects and constraints of salted fish processing business. The research method used was a survey by takeing an activity/case study and determine the respondents using census method.Based on this research, salted fish processing business activities in the form of inputs have sufficient availability, process and output runs regularly so as to produce output in the form of processed products salted fish ready for market. The total investment every month is Rp 76.952 million,- and profits every month is Rp 9.895.083. According to different eligibility criteria, this effort deserves to be continued and developed.Keywords: Business Analysis, Processing, Salted Fish, Pondok Batu